Synthesis and Characterization of Lignin-Silver Nanoparticles - Maršík, Dominik; Thoresen, Petter Paulsen; Maťátková, Olga; Masák, Jan; Sialini, Pavel; Rova, Ulrika; Tsikourkitoudi, Vasiliki; Christakopoulos, Paul; Matsakas, Leonidas; Jarošová Kolouchová, Irena (Molecules (Basel, Switzerland), 2024)
Metal nanoparticle synthesis via environmentally friendly methods is gaining interest for their potential advantages over conventional physico-chemical approaches. Herein, we propose a robust green synthesis route for lignin-modified silver nanoparticles, utilizing the recovery of lignin as a renewable raw material and exploring its application in valuable areas. Through a systematic approach combining UV-Vis spectroscopy with AAS and DLS, we identified repeatable and scalable reaction conditions in an aqueous solution at pH 11 for homogeneous silver nanoparticles with high uniformity. The TEM median sizes ranged from 12 to 15 nm with circularity between 0.985 and 0.993. The silver nanoparticles yield exceeded 0.010 mol L-1, comparable with traditional physico-chemical methods, with a minimal loss of silver precursor ranging between 0.5 and 3.9%. Characterization by XRD and XPS revealed the presence of Ag-O bonding involving lignin functional groups on the pure face-centered cubic structure of metallic silver. Moreover, the lignin-modified silver nanoparticles generated a localized thermal effect upon near-infrared laser irradiation (808 nm), potentially allowing for targeted applications in the biomedical field. Our study showcases the potential of lignin as a renewable reducing and capping agent for silver nanoparticle synthesis, addressing some shortcomings of green synthesis approaches and contributing to the development of suitable nanomaterials.
Keywords: plasmon resonance; green synthesis; lignin-silver nanoparticles